Perbaikan Tanah Gambut Dengan Metoda Kolom Konfigurasi Segitiga Dari Campuran Fly Ash Dan Bottom Ash - Imam Hanafi; Muhardi Muhardi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Stone column is a digging and replacement effort undertaken to replace soils to be used as base of construction with compacted vertical columns. In this research, column with fly ash and bottom ash mixtures with 40% fly ash and 60% bottom ash is used.The columns are used as reinforcement of peat soil with triangular pattern. Variations used are 3 cm, 4 cm, and 5,5 cm in diameter (D) with spaces 1,25D, 1,5D, and 1,75D. Loading test was performed to the stabilized peat soil and bearing capacity of the soil was analyzed by 20 mm settlement method and theoretical analysis suggested by Barksdale and Bachus (1983).Results of the 20 mm settlement method obtained maximum bearing capacity is given by 5,5 cm diameter and 1,25 D space variation. The maximum bearing capacity is 9,20 kg/cm2 with an increase of 51,07%. For theoretical analysis of single column, maximum bearing capacity is given by 3 cm diameter and for theoretical analysis of group columns, maximum bearing capacity is given by 5,5 cm diameter and 1,75 D space variation.Keywords : stone column, diameter, space, bearing capacity